New thinking to create level playing field - Abd Razak, Dzulkifli (2009)
THE Third Festival of Thinkers was held in Abu Dhabi recently with more that 200 experts congregating to discuss urgent issues facing the world today. Among them were at least 10 Nobel Prize laureates from 40 countries which included Professor John Nash, Dr Robin Warren and Professor Richard Ernst. Others who attended were King Carl XVI Gustaf of Sweden, Cherie Blair, Mike Moore, the former prime minister of New Zealand, legendary US basketball star Kareem AbdulJabbar and Dr Fidel Castro of Cuba.